Makna Kain Lawon dalam Tradisi Bonokeling: Kajian Interaksionisme Simbolik terhadap Warisan Budaya Lokal - Auliasari, Filza Nabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Lawon cloth in the Bonokeling indigenous community is not merely a burial shroud but a cultural symbol imbued with deep spiritual, social, and collective identity meanings. The use of Lawon is a sacred tradition passed down through generations and practiced in every death ritual with strict rules and symbolic interpretations, such as the odd number of layers representing levels of filial devotion. This study aims to explore the symbolic meaning of Lawon in the Bonokeling community using the theoretical framework of symbolic interactionism. The research employed a qualitative-descriptive approach through library research, utilizing relevant literature, and academic articles. The findings indicate that Lawon is collectively understood as a symbol of purity and spiritual fulfillment in the process of murca (the return of the body to the earth), as well as a marker of cultural identity that distinguishes the Bonokeling community from outsiders. The meaning of Lawon is constructed through social interaction, symbolic communication, and on going value interpretation with in the community. In conclusion, Lawon serves as a significant symbol that not only preserves cultural heritage but also reinforces the social structure and solidarity of the Bonokeling community through a dynamic and living process of meaning-making.Keywords : Lawon; Bonokeling; cultural symbol; symbolic interaction